Apprentices of freedom: Atlantic histories of the africanos livres in mid-nineteenth century Rio de Janeiro. Issue 2 (August 2015) - Nelson, Jennifer
Abstract : This article examines the journey undertaken by the slave ship Brilhante, captured by a British anti-slave trade patrol off the coast of Brazil in 1838. The ship and its crew were engaged in slave trafficking in contravention of international treaty agreements. In accordance with prize law the Brilhante was condemned by the Anglo-Brazilian mixed commission court in Rio de Janeiro and the slaves on-board were freed and apprenticed for a prescribed number of years. This article argues that during their apprenticeships not only were these Africans treated in the same way as slaves, but they formed similar bonds for survival. Both ethnic solidarity and shipmate bonds, which transcended ethnic boundaries, allowed them to forge new identities. The article demonstrates how the liberated Africans from the ship, who belonged to a larger marginalised group of "recaptives" within the Atlantic World, were thus able to facilitate the achievement of their eventual freedom, and improve the conditions in which they lived.